How to study linguistics - Finch, Geoffrey (London : MacMillan Press, 1998)
This book is about: Beginning linguistics; The linguistic context; Studying sound; Studying syntax; Studying meaning; Studying linguistics further; and How to write a linguistics essay.
Keywords: Linguistics; Linguistics -- Study and teaching